Identification of Postpartum Depression in an Online Community. Issue 5 (18th August 2015) - Teaford, Dominique; Goyal, Deepika; McNiesh, Susan G.
ABSTRACT: Objective: To identify the rate of postpartum depression symptoms in an online community. A secondary purpose was to identify women's experiences when accessing health care services for postpartum depression (PPD). Design: A quantitative, cross‐sectional, survey design. Setting: The setting consisted of nine birth clubs from one online community specifically targeted toward new mothers. Participants: A convenience sample of 469 mostly married ( n = 373), White ( n = 401) mothers with a mean age of 29.3 ( SD = 5.3) years took part in this study. The majority ( n = 433) reported living in the United States with access to health insurance coverage. Methods: The Edinburgh Postnatal Depression Scale (EPDS) was used to assess depression symptoms. Mothers indicating a previous diagnosis of PPD also completed the Access to Postpartum Depression Care (APDC) questionnaire. Results: Total EPDS scores ranged from 0 to 27 with a median of 7.0. Sixteen percent of participants ( n = 75) scored ≥ 13, indicating a high risk for developing PPD. Of these 75 mothers, 18 (24%) indicated having thoughts of harming themselves sometimes and five (7%) indicated having these thoughts quite often. Additionally, 76 mothers indicating a previous history of PPD also completed the APDC questionnaire. Findings suggested mothers often received care that did not meet their expectations. Barriers to PPD care included insurance limitations and insensitive comments from their health care providers. Conclusions: The rate of depression symptoms noted in this Internet‐based population is in agreement with published rates. Therefore, findings of this study support further exploration and evaluation of using online platforms for PPD screening.